Graft‐derived macrophage migration inhibitory factor correlates with hepatocellular injury in patients undergoing liver transplantation. Issue 6 (21st April 2017) - Baron‐Stefaniak, Joanna; Schiefer, Judith; Miller, Edmund J.; Plöchl, Walter; Krenn, Claus G.; Berlakovich, Gabriela A.; Baron, David M.; Faybik, Peter
Abstract: Experimental studies suggest that macrophage migration inhibitory factor (MIF) mediates ischemia/reperfusion injury during liver transplantation. This study assessed whether human liver grafts release MIF during preservation, and whether the release of MIF is proportional to the extent of hepatocellular injury. Additionally, the association between MIF and early allograft dysfunction (EAD) after liver transplantation was evaluated. Concentrations of MIF, aspartate aminotransferase (AST), alanine aminotransferase (ALT), lactate dehydrogenase (LDH), and creatine kinase (CK) were measured in effluents of 38 liver grafts, and in serum of recipients. Concentrations of MIF in the effluent were greater than those in the recipients' serum before and after reperfusion (58 [interquartile range, IQR:23‐79] μg/mL vs 0.06 [IQR:0.03‐0.07] μg/mL and 1.3 [IQR:0.7‐1.8] μg/mL, respectively; both P <.001). Effluent MIF concentrations correlated with effluent concentrations of the cell injury markers ALT ( R =.51, P <.01), AST ( R =.51, P <.01), CK ( R =.45, P =.01), and LDH ( R =.56, P <.01). Patients who developed EAD had greater MIF concentrations in effluent and serum 10 minutes after reperfusion than patients without EAD (Effluent: 80 [IQR:63‐118] μg/mL vs 36 [IQR:20‐70] μg/mL, P =.02; Serum: 1.7 [IQR:1.2‐2.5] μg/mL vs 1.1 [IQR:0.6‐1.7] μg/mL, P <.001). Conclusion: Human liver grafts release MIF in proportion to hepatocellular injury. Greater MIF concentrations in effluent and recipient's serum are associated with EAD after liver transplantation.